Enhanced photodegradation of methylene blue with alkaline and transition‐metal ferrite nanophotocatalysts under direct sun light irradiation. Issue 4 (28th October 2018) - Ali, Nauman; Zada, Amir; Zahid, Muhammad; Ismail, Ahmed; Rafiq, Misbha; Riaz, Aaisha; Khan, Adnan
Abstract : It is highly desired to synthesize low‐cost photocatalysts for the degradation of colored dyes to safeguard our environment for the future generations. Here, we report an extremely efficient and low‐cost synthesis of alkaline earth and transition‐metal ferrite photocatalysts (MgFe2 O4, CaFe2 O4, BaFe12 O19, CuFe2 O4, and ZnFe2 O4 ) from their chloride salts and their applications for the degradation of methylene blue (MB) dye under UV–visible and direct sunlight irradiation. The as‐prepared photocatalysts displayed enhanced photoactivities under both conditions of irradiation. After calcination at 600°C, the photocatalytic degradation increased significantly, and 96 and 85% MB was removed with ZnFe2 O4 under UV–visible and direct sunlight irradiation, respectively. Moreover, large amounts of hydroxyl free radicals were produced under both irradiation conditions, which participated in the degradation of MB. The enhanced photodegradation activities of these photocatalysts are attributed to their extended visible light absorption and low bandgaps. This work will provide a feasible route to the synthesis of efficient and low‐cost photocatalysts to utilize sunlight for environmental remediation. Abstract : Highly efficient metal ferrite nanophotocatalysts are prepared by a simple precipitation method. The excellent degradation efficiency for methylene blue has been attributed to the hydroxyl free radicals. This work shows that these nanophotocatalysts can be used for the degradation of pollutants under direct sunlight irradiation.